Integrated VES and GPR Investigation of Clay-Rich Units in the Çukurçeşme Formation (Şile, Istanbul) - Yalçın, Cihan; Canli, Hurşit; Kumral, Mustafa; Kaya, Mustafa; Sercan, Sercan (Universidad Nacional Autonoma de Mexico, 2026)
The present study reviews the subsurface distribution and geometry of clay-rich strata within the Oligo–Miocene Çukurçeşme Formation in the Şile area (Istanbul) using an integrated methodology combining Vertical Electrical Sounding (VES) and Ground Penetrating Radar (GPR). A total of 30 VES measurements were obtained and analyzed by 1D inversion, and the resultant models were assembled into 2D pseudosections to designate laterally continuous conductive layers. Low-resistivity zones seen across the profiles were interpreted as clay-dominant, aquiferous strata based on their distinctive electrical response and field observations. GPR data acquired with a 38–50 MHz antenna yielded high-resolution insights into the near-surface strata. Radargrams displayed continuous, moderately inclined reflectors indicative of the upper margins of clayey strata; however, signal attenuation restricted imaging at deeper levels. The integration of VES-derived resistivity structure with GPR reflections improved the interpretation of the clay layer's geometry and revealed thickness variations throughout the study area. The aggregated findings demonstrate that clay-rich strata often occur at depths of approximately 5 to 40 meters, with localized thickening influenced by structural and depositional factors. The concordance between VES and GPR interpretations enhances the credibility of the subsurface model generated in this work. This study demonstrates the efficacy of combining VES and GPR techniques to characterize diverse near-surface formations in regions where clay predominates, thereby influencing electrical and electromagnetic responses. The results establish a geophysical framework for subsurface characterization in analogous geological contexts and facilitate future research to enhance the stratigraphic and structural understanding of the Çukurçeşme Formation.